Isaac Díaz Pardo and The Arts - Cantera Montenegro, Jesús (Madrygal. Revista de Estudios Gallegos, 2004)
The present article tells the relation between Isaac Díaz Pardo and the Arts, starting from the title page’s illustration of this number of Madrygal. Galician arts, painting, ceramics.